Evaluation of Lead Ion in the Wastewater of the Lifting and Treatment Stations Using ICP-MS and CPE Methods - Hussain, Mohammed Nasser; Khudhair, Ahmed Fadhil; Ahmed, Hussain Jawad (Indonesian Journal of Chemistry, 2024)
To pre-concentrate trace amounts of lead before determining it by UV-vis spectrophotometer, a new method for micelle-mediated phase separation has been created. The process depends on the extraction of lead from iodine media using Triton X-114 in the cloud point extraction method without the need for any chelating agents, where the optimal conditions for the method were achieved, which temperature 50 °C, pH 4, and 30 mmol L−1 concentration of KI, 0.3 mL of 2% (v/v) Triton X-114, and time of 10 min in the water bath. Linearity was followed between 1 and 16 µg/mL of lead concentration. The method's lead detection limit is 0.1 µg/mL and %RSD 3.633. Additionally, the interference impact of certain cations was evaluated. The proposed technique was successfully applied to determine the lead ion in the wastewater in ten different stations in the center and district of Al-Hur in Karbala City. The lead ion of the wastewater of the stations under study was also determined directly using inductively coupled plasma-mass spectrometry (ICP-MS) technology comparing its results with the new method and performing the statistical analysis of both methods. The p-value was less than 0.05, showing significant differences between both methods.